Stategi Pengembangan Agrowisata Catra Strawberry Kabupaten Wonosobo - Daffa, Naufal; Budiraharjo, Kustopo; Mukson, Mukson (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
The research aims to analyze the strengths, weaknesses, opportunities, and threats of Catra Strawberry Agrotourism and formulate priority development strategies of Catra Strawberry Agrotourism. The research location is Catra Strawberry Agrotourism in Binangun Hamlet, Wringinanom, Kertek, Wonosobo Regency. The research method used was the case study method with purposive sampling for 8 key people and accidental for 22 visitors with a total of 30 respondents. The key persons in this research are five agrotourism administrators, one person from Wringinanom Village, one person from the Wonosobo Regency Food, Agriculture and Fisheries Service, and one person from the Wonosobo Regency Tourism and Culture Office. The data analysis methods used are the Internal Strategic Factors Analysis Summary (IFAS) matrix, the External Strategic Factors Analysis Summary (EFAS) matrix, the Strength Weakness Opportunity Threat (SWOT) matrix, and the Quantitative Strategic Planning Matrix (QSPM). The research results show that the highest internal strength of Catra Strawberry Agrotourism is the free entrance ticket price and the biggest weakness is the lack of road signs/wall signs. Analysis of external factors shows that the opportunity that has the highest prospect of being achieved is the increasing number of visitors during holidays and the biggest threat to agrotourism is the decline in tourist interest. Based on the SWOT analysis, it was found that Catra Strawberry Agrotourism is in quadrant 1 and can use aggressive or growth-oriented strategies. The priority strategy with the highest attractiveness value is optimizing social media for marketing and increasing promotions.